Numerical methods and applications : 8th International Conference, NMA 2014, Borovets, Bulgaria, August 20-24, 2014, Revised selected papers /: 8th International Conference, NMA 2014, Borovets, Bulgaria, August 20-24, 2014, Revised selected papers. (2015) - Unknown
No abstract available